2001
DOI: 10.1002/1521-4095(200109)13:18<1407::aid-adma1407>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Catalytic Materials with Organic Frameworks

Abstract: Organic frameworks have tempting properties for nanostructured heterogenous catalysts with active sites that are size‐ and pH‐tunable, yet working examples are sparse. The authors present a promising structure type, i.e., cross‐linked assemblies of lyotropic liquid crystals (LLCs), whose polar termini form ordered channels with enhanced basic or acidic catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…Organic liquidcrystalline materials themselves had not been used as catalysts until Gin and co-workers reported catalytic amphiphilic liquid crystals. [276][277][278][279][280] They showed that cross-linked, lyotropic liquid-crystalline (LLC) assemblies function effectively as catalytic platforms ( Figure 28). In these systems, the reactive head groups of amphiphilic molecules are concentrated at the center of the cylinder in the lyotropic inverted hexagonal phase (H II ).…”
Section: Catalysis and Templates For Synthesismentioning
confidence: 99%
“…Organic liquidcrystalline materials themselves had not been used as catalysts until Gin and co-workers reported catalytic amphiphilic liquid crystals. [276][277][278][279][280] They showed that cross-linked, lyotropic liquid-crystalline (LLC) assemblies function effectively as catalytic platforms ( Figure 28). In these systems, the reactive head groups of amphiphilic molecules are concentrated at the center of the cylinder in the lyotropic inverted hexagonal phase (H II ).…”
Section: Catalysis and Templates For Synthesismentioning
confidence: 99%
“…Polyelectrolyte Templating** By Qi Li, John F. Quinn, and Frank Caruso* Materials containing nanopores are important in a variety of fields, including catalysis, [1,2] separations, [3,4] electronics, [5] optics, [6] and biomaterials engineering. [7,8] Templating techniques represent an effective method for producing such materials (both inorganic and organic) with controlled pore structures.…”
Section: Nanoporous Polymer Thin Films Viamentioning
confidence: 99%
“…In addition to their intensive applications based on their host−guest chemistry, macrocycles have also been used as building blocks to construct solid materials including porous organic polymers (POPs), metal–organic frameworks (MOFs), and crystalline organic materials (COMs) . Particular attention should be paid to COMs, a class of organic materials featuring facile preparation, high crystallinity, structural diversity, chemical stability, solution‐processability, etc . Different from MOFs that are composed of both inorganic (metal ions) and organic species (organic ligands) through coordination, COMs refer to a kind of crystalline materials composed of pure organics connected by either covalent or noncovalent bonds .…”
Section: Introductionmentioning
confidence: 99%